Delivery of Small Genetic Molecules through Hollow Porous Nanoparticles Silences Target Gene and in Turn Stimulates Osteoblastic Differentiation. (16th August 2016) - Kim, Jung‐Ju; Singh, Rajendra K.; Patel, Kapil D.; Kim, Hae‐Won
Abstract : Nanocarriers are one of the key elements to improve the therapeutic potential of signaling molecules, including genes for the disease treatment and tissue repair. Here, a nanocarrier system is reported that delivers genetic molecule small interference RNA (siRNA) for osteoblastic stimulation. For this, a hollow form of mesoporous silica nanoshell (MSns) is designed to load and release siRNA to silence Plekho‐1 gene. In particular, a pressure‐induced loading method is effective in enhancing the incorporation of siRNA within a hollow space; a loading level attained ≈30% is almost three times higher than that of a non‐hollow form. Furthermore, the release of siRNA from the nanocarriers is highly sustainable; continued over 18 d in a diffusion‐controlled manner, in striking contrast to the rapid release (3 d) from a non‐hollow form. The nanocarriers exhibit excellent cell viability, and the siRNA‐nanocarrier complexes are efficiently internalized to osteoblastic cells (uptake level over 90%). The intracellular delivery suppresses the target gene Plekho‐1 expression down to 20%, which in turn up‐regulates the expression of osteoblast transcriptional factors (Runx2 and Smad2), demonstrating an effective gene delivery system for bone repair. Abstract : The mesoporous hollow form of a silica nanoparticle is developed to load small interfering RNA (siRNA) at high quantity and to deliver it intracellularly in a sustainable manner. The nanoparticle/gene complexes are demonstrated to silence Plekho‐1 siRNA in osteoblastic cells effectively, and to then ultimately stimulate the differentiation of osteoblasts, proving to be a promising nanocarrier system for bone repair.